2022
DOI: 10.3390/foods11152379
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heavy Metal Uptake in Potatoes Cultivated in a Typical Karst Landform, Weining County, China

Abstract: The average content of heavy metals in Weining soil of karst landforms is generally higher than that of other agricultural regions. The aim of this study was to evaluate the heavy metal content in potatoes from Weining county and to analyze the correlation between the content of heavy metals in potatoes planted in the soil of karst landform and the soil’s environmental factors (soil heavy metals, soil pH, soil organic matter, altitude). Weining county (Guizhou province, China) is a typical karst landform, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Heavy metal concentrations in soils and the order in which they are found vary from one place to another because the heavy metal content of the soil depends on a wide range of factors relating to lithogenic and anthropogenic sources [45] . For example, in mining areas in Weining County in China, the soil in which potatoes are grown contains the heavy metals considered in our study, concentrated in the following order: Cr (119 mg/kg) > Pb (59.3 mg/kg) > Ni (50.8 mg/kg) > Cu (47.8 mg/kg) > As (25.8 mg/kg) [24] > Cd (2.60 mg/kg) [46] . In our study, as can be seen from Table S4 , the concentration order of heavy metals in the potato-growing soil was Al (13,127.84 mg/kg) > Mn (509.248 mg/kg) > Ba (187 mg/kg) > Cu (51.38 mg/kg) > As (23.607 mg/kg) > Pb (16.861 mg/kg) > Ni (10.199 mg/kg) > Cr (9.798 mg/kg) > Cd (0.352 mg/kg).…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Heavy metal concentrations in soils and the order in which they are found vary from one place to another because the heavy metal content of the soil depends on a wide range of factors relating to lithogenic and anthropogenic sources [45] . For example, in mining areas in Weining County in China, the soil in which potatoes are grown contains the heavy metals considered in our study, concentrated in the following order: Cr (119 mg/kg) > Pb (59.3 mg/kg) > Ni (50.8 mg/kg) > Cu (47.8 mg/kg) > As (25.8 mg/kg) [24] > Cd (2.60 mg/kg) [46] . In our study, as can be seen from Table S4 , the concentration order of heavy metals in the potato-growing soil was Al (13,127.84 mg/kg) > Mn (509.248 mg/kg) > Ba (187 mg/kg) > Cu (51.38 mg/kg) > As (23.607 mg/kg) > Pb (16.861 mg/kg) > Ni (10.199 mg/kg) > Cr (9.798 mg/kg) > Cd (0.352 mg/kg).…”
Section: Resultsmentioning
confidence: 81%
“…Few studies include altitude as a factor in the analysis of heavy metal content in potatoes, and even fewer in mining areas. In an area of abundant ore deposits in Weining County, China, altitude was found not to have a significant influence (p < 0.05) on the Pb, Cr, Ni and As concentrations in potatoes grown between 2151 and 2744 m.a.s.l., but lower altitudes favored the accumulation of Cd and Cu [24] , [46] .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the present study, all the BCF values determined were below 1, and this finding indicates that the transfer of metals from the soil to native potatoes is low in the experimental area. Shi et al [64] found similar BCF values for Zn, Cu, Pb and Cr in potatoes, suggesting that the potato's ability to absorb metals is very low (BCF ≤ 1), and it does not accumulate them in its tissues [100] . The higher the BCF, the greater the transfer of heavy metals from the soil to plant tissues [66] .…”
Section: Resultsmentioning
confidence: 95%
“…The BCF was calculated using Eq. (3) [64] : where and are the content of heavy metals in potato tubers and soils (mg kg −1 ), respectively.…”
Section: Materials and Methodologymentioning
confidence: 99%